Design and Performance Evaluation of Small Scale Corn Shelling Machine - Chu, Pan Chu (AI Society & STMIK Indonesia, 2024)
This paper focuses on the design and performance evaluation of small scale corn shelling machine. The motor power of the corn shelling machine is 0.75 hp and rotational speed is 1400 rpm. This motor used v-belt transmission system to drive the shelling cylinder shaft. The number of a belt is used in this transmission system. The standard diameter of the corn shaft is 25 mm. The ASME code equation is used to design the shaft for corn shelling machine. Single-row deep groove ball bearing is selected for left and right bearing of corn shaft. The average shelling efficiency, output capacity and damage efficiency of corn were compared with difference spike teeth and various speeds. The average shelling efficiency of 24, 27 and 30 spike teeth are 87 %, 94 % and 81 %. The average output capacity of 24, 27 and 30 spike teeth are 232 kg/h, 281 kg/h and 263 kg/h. The average damage efficiency of 24, 27 and 30 spike teeth are 13 %, 6 % and 19 % respectively. The maximum shelling efficiency and output capacity are found 27 spike teeth at cylinder speed of 690 rpm. The minimum damage efficiency is 6% at 27 spike teeth.